A review on the reactivation of hardened cement paste and treatment of recycled aggregates. Issue 10 (5th July 2019) - Ohemeng, Eric A.; Ekolu, Stephen O.
Abstract : The generation of construction and demolition waste (CDW) worldwide keeps on escalating due to growth in infrastructure and the related refurbishment or replacement of existing structures. Numerous research studies on the utilisation of CDW materials in the production of new concrete have been conducted, from which it has been established that their use generally leads to inferior mechanical properties of the resulting concrete. As such, the general acceptance and conventional utilisation of CDW in the construction industry is undermined. The concept of a triple-layered interfacial transition zone is suggested to be the main reason for the inferior mechanical properties exhibited by recycled aggregate (RA) concrete. Past research on the reactivation of hydrated cement paste and on improving the quality of RAs by the use of different treatments, was reviewed. The review revealed that a combination of mechanical grinding and thermal treatment at temperatures of 500–800°C is an effective means of activating the cementitious properties of hardened cement paste. Adhered mortar removal and mortar fortification are the main approaches for enhancing the properties of RAs. Mechanical abrasion and/or thermal treatment at a temperature of 500°C, are the most effective techniques for improving the properties of RAs.